Method for analyzing and controlling nanodiamond particle concentration in composite plating solution
Patent Information
- Application Number
- JP2019090653
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-05-13
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2039-05-13
AI Technical Summary
【0009】 本発明によれば、複合めっき液中のナノダイヤモンド粒子濃度を、簡易かつ迅速に分析することができ、この分析方法を利用する本発明の複合めっき液の管理方法によれば、ナノダイヤモンド粒子の濃度の分析値をリアルタイムでナノダイヤモンド粒子の添加制御に反映させて、良好なめっき工程の維持管理のもとに、所望の特性を有する複合めっき皮膜を容易に得ることが可能になる。
Smart Images

Figure 0007626414000001 
Figure 0007626414000002 
Figure 0007626414000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for analyzing and controlling the concentration of nanodiamond particles in a composite plating solution.
[0002] In this specification, nanodiamonds may be referred to as "ND." [Background technology]
[0003] A composite plating solution in which nanodiamond particles are mixed and dispersed in a normal plating solution is known (Patent Document 1). By using a composite plating solution containing nanodiamond particles, a plating film in which the nanodiamond particles are uniformly dispersed is formed, which can improve the design, mechanical properties, and functionality of the plating film.
[0004] In order to reproducibly form a plating film having the desired characteristics using such a composite plating solution, it is necessary to control the concentration of nanodiamond particles in the composite plating solution, add nanodiamond particles to the composite plating solution appropriately so that this concentration becomes the specified concentration, and maintain and control the nanodiamond particle concentration.
[0005] The concentration of nanodiamond particles in the composite plating solution can be estimated, for example, by quantifying the amount of nanodiamond particles in the plating film, but this method requires complicated operations. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2018-83960 A Summary of the Invention [Problem to be solved by the invention]
[0007] The object of the present invention is to quickly and accurately analyze the concentration of nanodiamond particles in a composite plating solution using a simple method, and to appropriately manage the composite plating solution. [Means for solving the problem]
[0008] The present invention provides the following method for analyzing and controlling the concentration of nanodiamond particles in a composite plating solution. [1] A method for analyzing the concentration of nanodiamond particles in a composite plating solution, comprising the steps of measuring the absorbance of a composite plating solution containing nanodiamond particles and determining the concentration of the nanodiamond particles based on the measured absorbance, wherein the absorbance is measured at a wavelength selected from the range of 250 to 630 nm. [2] A method for controlling the concentration of nanodiamond particles in a composite plating solution, comprising analyzing the concentration of nanodiamond particles in the composite plating solution using the method of [1], and adding nanodiamond particles to the composite plating solution as necessary so that the concentration becomes a predetermined concentration. Effect of the Invention
[0009] According to the present invention, the concentration of nanodiamond particles in a composite plating solution can be easily and quickly analyzed, and according to the composite plating solution management method of the present invention which utilizes this analysis method, the analytical value of the nanodiamond particle concentration can be reflected in the addition control of the nanodiamond particles in real time, making it possible to easily obtain a composite plating film having the desired characteristics while maintaining and managing the plating process well. [Brief description of the drawings]
[0010] [Figure 1] Absorbance of copper plating solution (ND=0 ppm) without the addition of nanodiamond particles. [Diagram 2] Absorbance of copper plating solution (ND=50-1000ppm) to which nanodiamond particles have been added at a specified concentration. [Diagram 3] Absorbance of nanodiamond water dispersion (50 ppm, 500 ppm). [Figure 4] Calibration curve for copper plating solution with various concentrations of nanodiamond particles (ND=300-360ppm) added. [Diagram 5]Absorbance of nickel plating solution without added nanodiamond particles (ND=0 ppm). [Figure 6] Absorbance of nickel plating solution (ND=50-1000ppm) with nanodiamond particles added at a specified concentration. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In this specification, the composite plating bath contains a base metal plating solution and nanodiamond particles (ND particles). The concentration of the ND particles in the base metal plating bath is, for example, in the range of 0.001 to 1.0 g / L (the lower limit is preferably 0.003 g / L, more preferably 0.006 g / L, even more preferably 0.01 g / L, and particularly preferably 0.03 g / L. The upper limit of the concentration of the ND particles is preferably 0.8 g / L, more preferably 0.6 g / L, and particularly preferably 0.5 g / L), and is preferably 0.01 to 0.5 g / L.
[0012] The base metal is at least one selected from the group consisting of iron, nickel, zinc, copper, tin, aluminum, tungsten, molybdenum, tantalum, magnesium, cobalt, bismuth, cadmium, titanium, zirconium, antimony, manganese, beryllium, chromium, germanium, vanadium, gallium, hafnium, indium, niobium, rhenium, and thallium, preferably at least one selected from the group consisting of copper, nickel, zinc, tin, chromium, and permalloy, more preferably at least one selected from the group consisting of copper, nickel, zinc, and tin, and particularly preferably copper and nickel.
[0013] The particle size (D50) of the ND particles in the composite plating solution is, for example, 95 nm or less, preferably 70 nm or less, particularly preferably 60 nm or less, and most preferably 50 nm or less. The lower limit of the particle size (D50) of the ND particles is, for example, 20 nm.
[0014] Base metal plating solutions are known, and a composite plating bath can be obtained by adding ND particles or a dispersion thereof to a known base metal plating solution. The dispersion of ND particles is preferably an aqueous solution. The composite plating bath may be either an electrolytic composite plating bath or an electroless composite plating bath. The composite plating bath contains a water-soluble base metal salt and ND particles as essential components, and may further contain other components selected from a conductivity salt, a complexing agent, a reducing agent (electroless plating bath), an anode dissolution accelerator (in the case of a composite electrolytic plating bath), a phosphorus source (in the case of electroless nickel-phosphorus alloy plating), a pH buffer, a surfactant, a stabilizer, and an additive for adjusting the appearance and physical properties of the film (brightening agent, leveling agent, stress reducer, etc.). The water-soluble base metal salt exists as a base metal ion in the base metal plating bath. In addition, it may exist as an oxygen acid ion of the base metal or a base metal complex ion combined with a complexing agent. The concentration of the water-soluble base metal salt in the composite plating bath is, for example, 0.01 to 0.5 mol / L, and preferably 0.05 to 0.2 mol / L, calculated as the concentration of the base metal ions supplied to the composite plating solution.
[0015] The reducing agent contained in the electroless composite plating solution may be phosphonic acid or a phosphonate (e.g., an alkali metal phosphonate such as sodium phosphonate), phosphinic acid or a phosphinate (e.g., an alkali metal phosphinate such as sodium phosphinate), etc. When a phosphinate or a phosphonate is used as the reducing agent, the concentration of the phosphinate or the phosphonate in the electroless composite plating solution is, for example, 0.02 to 0.5 mol / L, and preferably 0.1 to 0.2 mol / L.
[0016] Examples of the complexing agent contained in the electrolytic and electroless base metal plating baths include citric acid, lactic acid, malic acid, glycolic acid, and salts thereof. Examples of citric acid include alkali metal citrates such as sodium citrate and potassium citrate. When citric acid and / or its salts are used, the concentration of citric acid and / or its salts in the electrolytic and electroless base metal plating baths is, for example, 0.02 to 1.0 mol / L, and preferably 0.1 to 0.5 mol / L.
[0017] The pH of the base metal plating bath is, for example, 5 to 11.
[0018] In the present invention, among the components of the composite plating solution, the ND particles are controlled. The components other than the ND particles can be controlled according to the usual method.
[0019] In a preferred embodiment of the present invention, examples of plating solutions for plating base metals other than ND particles include a base metal sulfate plating solution containing ND particles, base metal sulfates, sulfuric acid, chloride ions, etc.; a base metal cyanide plating solution containing a base metal cyanide, sodium cyanide, alkali carbonate, Rochelle salt, etc.; and a base metal pyrophosphate plating solution containing a base metal pyrophosphate, potassium pyrophosphate, ammonia water, potassium nitrate, etc.
[0020] The surface of the ND particles may have a hydrophilic functional group such as OH, COOH, or NH2. In addition, ND particles to which a hydrophilic group has been introduced via these functional groups may be used. Examples of hydrophilic groups include C-glycerin, polyglycerin (PG), ethylene glycol, propylene glycol, and butylene glycol. 2-4 Poly(C) such as alkylene glycol, polyethylene glycol, polypropylene glycol, and polybutylene glycol 2-4 These hydrophilic ND particles are either publicly known or can be produced by publicly known methods.
[0021] The ND particles may be blended in the (composite) plating bath as a solid, or as an ND particle dispersion liquid. The ND particle concentration in the ND particle dispersion liquid is, for example, about 1 to 100 g / L.
[0022] As the ND particles, hydrophilic ND particles coated or modified with a hydrophilic polymer are preferred from the viewpoint of excellent dispersibility, and hydrophilic ND particles having a water-soluble polymer containing a polyglycerin chain are particularly preferred.
[0023] The ND particle concentration in the composite plating solution of the present invention can be analyzed as follows. (i) First, for a composite plating solution in which the concentration of ND particles is to be analyzed, multiple types of composite plating solutions with known ND particle concentrations are prepared by blending ND particles in various blending amounts within the range in which the ND particle concentration is to be controlled. (ii) Next, the absorbance of each of the composite plating solutions prepared in (i) above is measured. (iii) Based on the results of (ii) above, a calibration curve showing the relationship between the absorbance of the composite plating solution and the ND particle concentration is prepared, as shown in FIG.
[0024] The wavelength for measuring the absorbance of the composite plating solution is selected from the range of 250 to 630 nm, and within this range, a calibration curve can be prepared at any wavelength to analyze the ND particle concentration in the composite plating solution. The wavelength for preparing the calibration curve is preferably a wavelength at which the absorbance change is large when the concentration of ND particles is increased, based on a plating solution that does not contain ND. For example, in the case of the copper plating solution shown in Figures 1 to 3, the wavelength is preferably 280 nm to 630 nm, more preferably 300 nm to 600 nm, and even more preferably 310 nm to 500 nm. In addition, in the case of the nickel plating solution shown in Figures 5 to 6, the wavelengths are preferably 300 nm to 370 nm and 430 nm to 580 nm, more preferably 305 nm to 360 nm and 440 nm to 560 nm, and even more preferably 310 nm to 350 nm and 440 nm to 550 nm. Even in the case of a copper plating solution and a nickel plating solution, if the components and concentrations contained in the plating solution change, the preferred wavelength for preparing the calibration curve may change. In addition, when the type of base metal in the base metal plating solution is changed from copper and nickel to other base metals such as iron, zinc, tin, aluminum, tungsten, molybdenum, tantalum, magnesium, cobalt, bismuth, cadmium, titanium, zirconium, antimony, manganese, beryllium, chromium, germanium, vanadium, gallium, hafnium, indium, niobium, rhenium, and thallium, the preferred wavelength for creating the calibration curve may also change. The preferred wavelength for creating the calibration curve can be easily determined by referring to the results of the copper plating solution and the nickel plating solution. The calibration curve may be created using only one wavelength, or may be created using multiple wavelengths (preferably two or three wavelengths). As shown in FIG. 3, the absorbance of the aqueous dispersion of ND particles is also greatly affected by the concentration of ND particles, so it is preferable to determine the wavelength for creating the calibration curve by taking this into consideration. Within the range of the ND particle concentration to be managed, the measurement wavelength of absorbance advantageous for determining the ND particle concentration is determined by the calibration curve. The concentration of ND particles in the composite plating solution can be analyzed from the measured absorbance value using a previously prepared calibration curve.The analysis of the ND particle concentration may be performed to identify the concentration of the ND particles, or may be performed in a concentration zone to determine whether the ND particle concentration may deviate from the acceptable range and ND particles should be added to the composite plating solution, for example in the form of an aqueous dispersion.
[0025] In the method for managing the ND particle concentration in the composite plating solution of the present invention, the composite plating solution is sampled from the plating tank, and the concentration of ND particles in the composite plating solution is analyzed by the method described above. If it is determined based on the analysis result that the ND particle concentration will remain within the allowable range until the next sampling, ND particles are not added, but if it is determined based on the analysis result that the ND particle concentration may fall outside the allowable range at the time of the next sampling, ND particles are added to the composite plating solution in the plating tank as necessary, for example in the form of an aqueous dispersion, so that plating is performed with an ND particle concentration within the allowable range.
[0026] Regarding the method for managing the ND concentration of the present invention, for example, the concentration of ND particles may be automatically managed by a system including a sampling means for sampling the plating solution from the composite plating solution using a pump or the like, an analysis means for measuring the absorbance of the sampled sample, a control means for receiving a signal resulting from the analysis means and determining whether or not ND particles are to be added to the composite plating solution and the amount to be added, and an ND particle adding means for controlling the addition of ND particles by the control means. Alternatively, a manager may manually sample the composite plating solution and measure the absorbance at an appropriate time while observing the plating status, and based on the results, determine whether or not ND particles need to be added to the composite plating solution and, if so, the amount to be added. EXAMPLES
[0027] The present invention will now be described in more detail with reference to examples. Example 1 Composite plating solutions with various ND concentrations were prepared by adding an aqueous dispersion of ND particles (PG-ND particle aqueous dispersion (manufactured by Daicel Corporation)) that had been hydrophilized by modification with polyglycerin (PG) to a copper plating solution (product name "Electrolytic Plating Solution" manufactured by Kiyokawa Plating Industry Co., Ltd.) so that the PG-ND concentrations in the copper plating solution were 0, 50, 100, 200, 300, 400, 500, and 1000 ppm.
[0028] The absorbance of the obtained composite copper plating solution was measured at wavelengths of 300 nm, 310 nm, 320 nm, 330 nm, 340 nm, 350 nm, 355 nm, and 360 nm using a spectrophotometer (U-3900H Spectrophotometer manufactured by Hitachi High-Tech Fielding Corporation), and a calibration curve was created (Figure 4). Figure 1 shows the absorbance measurement results of the copper plating solution to which PG-ND was not added, and Figure 2 shows the absorbance measurement results of the copper plating solutions to which PG-ND was added at 50 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, and 1000 ppm, respectively. Figure 3 shows the absorbance of the PG-ND aqueous dispersion when the PG-ND concentration was 50 ppm and 500 ppm.
[0029] The results in Figure 4 show that the concentration of ND particles can be determined by absorbance and that the concentration of ND particles in the composite plating solution can be appropriately controlled.
[0030] Example 2 Composite plating solutions with various ND concentrations were prepared by adding an aqueous dispersion of ND particles (PG-ND particle aqueous dispersion (manufactured by Daicel Corporation)) that had been hydrophilized by modification with polyethylene glycol (PG) to a nickel plating solution (product name "Electrolytic Nickel Plating Solution" manufactured by Kiyokawa Plating Industry Co., Ltd.) so that the PG-ND concentrations in the copper plating solution were 0, 50, 100, 200, 300, 400, 500, and 1000 ppm.
[0031] The absorbance of the obtained composite copper plating solution was measured using a spectrophotometer. Figure 5 shows the absorbance measurement results of the copper plating solution to which PG-ND was not added, and Figure 6 shows the absorbance measurement results of the copper plating solutions to which PG-ND was added at 50 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, and 1000 ppm, respectively.
[0032] The results in Figures 5 and 6 reveal that the concentration of ND particles can be determined by absorbance and that the concentration of ND particles in the copper plating solution can be appropriately controlled.
Claims
1. The method includes a step of measuring the absorbance of a composite plating solution containing nanodiamond particles and a base metal, and determining the concentration of the nanodiamond particles based on the measured absorbance; the base metal is copper or nickel; When the base metal is copper, the wavelength for measuring absorbance is selected from the range of 310 nm to 500 nm; When the base metal is nickel, the wavelength for measuring absorbance is selected from the ranges of 300 nm to 370 nm and 430 nm to 580 nm.
2. A method for managing the concentration of nanodiamond particles in a composite plating solution, comprising analyzing the concentration of nanodiamond particles in the composite plating solution using the method of claim 1, and adding nanodiamond particles to the composite plating solution as necessary so that the concentration becomes a predetermined concentration.
Citation Information
Patent Citations
Method for measuring nano particle content in electroplate liquid or layer by spectrophotometer
CN1786686A
Automatic analyser and controller of electroless composite plating liquid
JP2002047575A
Composite plating solution having diamonds particle dispersed therein, and method for producing the same
JP2011149071A
Concentration measuring method for dye-based additive in copper sulfate plating solution, plating method, and plating device
JP2013053338A
Method for regenerating metal plating solution, method for regenerating washing water used in metal plating, plating apparatus and regenerating material for metal plating
JP2017179604A